تصميم زي جراحي موحد لطالبات الكليات الصحية مستوحى من الأزياء التقليدية - العقل، وسمية بنت عبدالرحمن بن مطلق; العجاجي، تهاني بنت ناصر بن صالح (جامعة الكويت - مجلس النشر العلمي, 2021)
الأهداف: تحديد مواصفات الزي الجراحي المقترح لطالبات الكليات الصحية، وإبراز أهمية وجمال الأزياء التقليدية، والاستفادة منها في تصميم الأزياء الجراحية، من خلال توظيف خطوطها وزخارفها وأقمشتها في ابتكار تصميمات لزي جراحي ذي سمات مميزة وظيفيا وجماليا. المنهج: يتبع في هذا البحث المنهج الوصفي التطبيقي، ويتكون مجتمع البحث من طالبات الكليات الصحية في جامعة الأميرة نورة بنت عبد الرحمن، وتشمل الأساليب والأدوات المستخدمة في جمع المادة العلمية الاستبانة الموجهة للطالبات لاستطلاع آرائهن وملاحظاتهن حول التصميمات المقترحة. النتائج: تصميم مجموعة من الأزياء الجراحية مستوحاة من الأزياء التقليدية، وزخرفة أقمشتها بزخارف تقليدية، وتتميز بالراحة والاحتشام، مستمدة من خطوط الأزياء التقليدية الواسعة وبالخامات الطبيعية الفاتحة المناسبة لأجواء المملكة العربية السعودية، المزينة بالزخارف التقليدية، لرفع الانتماء والحس الوطني لدى العاملات بالمجال الصحي. الخاتمة: يتطلب تصميم الزي الجراحي مراعاة الجانبين الوظيفي والجمالي، إذ لهما دور كبير في أداء الكادر الصحي عمله بجودة عالية.
Objectives: This research aims to determine the characteristics of the proposed surgical uniform for girl students of health colleges. It also highlights the importance and beauty of traditional costumes, viewing the possibility of using them in designing surgical costumes by using the lines, decorations and fabrics to create innovative designs for surgical uniforms with functional and aesthetic features Method: This study conducts the applied descriptive approach, as the study sample includes students of Health Faculties at Princess Nourah bint Abdulrahman University. Methods and tools used in scientific data collection include a questionnaire addressed to the students to ask for their opinions and notes and comments on the proposed designs. Results: Designing a collection of surgical costumes inspired by traditional costumes, and the decorations of their fabrics with traditional motifs, characterized by comfort and modesty, and derived from the wide trends of traditional costumes and bright natural materials appropriate to the context of Saudi Arabia, decorated with traditional motifs to enhance patriotism and national pride among health workers. Conclusion: Designing a surgical uniform requires considering both the functional and aesthetic aspects, as they have a great role in the performance of the health staff. Key recommendations included developing uniforms in the public and private sectors to cope with the functional requirements of the work and to obtain aesthetic look and enhance the sense of national belonging. The recommendations also draw the attention of the designers to create fashionable designs that combine new ideas, functional requirements and traditional heritage when designing uniforms.
Keywords: تصميم الأزياء -- الزي الموحد -- طالبات الكليات الصحية -- الأزياء التقليدية